Academic-adjustment and gender: personal-resources and cognitive-resources, satisfaction and burnout among men and women - Kaim, Zeev; Romi, Shlomo (Frontiers in Education, 2025)
IntroductionAccording to the Identity Capital Model and the Salutogenic Model students’ academic-adjustment is affected by their emotions during their studies and by personal-resources and cognitive-resources. Two academic-adjustment measures examined here: Intention to complete a BA and intention to pursue an advanced degree – to explain the variance in academic-adjustment measures. As gender is a significant affecting variable on academic-adjustment, gender differences were related to academic-adjustment measures.MethodsParticipants were undergraduate university and college students of education, 189 men and 209 women. Participants answered questionnaires regarding demographic characteristics, personal-resources and cognitive-resources, motivation, satisfaction, burnout, and academic-adjustment.ResultsThe findings revealed that students’ sense-of-threat and sense-of-challenge were major contributors to academic-adjustment level and perceived academic efficacy. Similarities between men and women for academic-adjustment were found for demographic characteristics, personal-resources, burnout, and intention to complete BA. However, cognitive measures and motivation differed by gender, with sense-of-threat and sense-of-challenge contributing to explaining women’s variance only; motivation contributed directly to women’s academic-adjustment and only indirectly to men’s due to their sense-of-challenge.DiscussionThe differences indicate variance in the academic-adjustment factors among men and women, pointing to the need for further research and constructing unique adjustment interventions for each group.